The Role of Communication in Empowering Women-Led MSMEs: A Narrative Literature Review - Wardani, Rimayanti (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This narrative literature review examines the multidimensional role of communication in empowering women-led Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Twenty empirical studies were analyzed to identify how communication shapes digital engagement, organizational dynamics, empowerment processes, and community-based networking. The findings show that communication is not merely a technical tool but an integrated mechanism that supports market expansion, entrepreneurial identity formation, decision making, capacity building, and business resilience. Digital communication enhances visibility and competitiveness, while organizational and interpersonal communication strengthen leadership, coordination, and well-being. Communication within empowerment programs facilitates learning and motivation, and community-based communication provides collective support that reinforces women’s entrepreneurial agency. Despite these strengths, the literature remains largely descriptive and lacks empirical evaluation of communication effectiveness, longitudinal perspectives, and analysis of gender-based communication barriers. Future research should examine specific communication models, assess long-term outcomes, and explore digital storytelling and influencer-based strategies to advance women’s MSME development. This review contributes an integrated framework that highlights communication as a central driver of women’s entrepreneurial empowerment and sustainability.